Implementasi Model Pendidikan Islam Terpadu di SMP Islam Hidayatullah Pule Trenggalek - Ibnu Waqfin, Mohammad Saat; Fatayati, Rida (Universitas KH. A. Wahab Hasbullah, 2024)
Education is a very important part for someone in preparing themselves in the future, in order to be able to adjust as well as possible with the surrounding environment. Basically not only general education given to the students but also religious education is very important, because it is a very effective effort to reduce negligence or negative behavior of students. In addition to religious education students can gain a stronger foundation of faith so as not to be easily influenced by things that are not good. This study explains that the concept of integrated Islamic education is a process of applying the approach of education implementation by mamadukan general education with religious education into a bundle of curriculum. Integrated Islamic education emphasizes cohesiveness in learning so that it can optimize the cognitive, affective and psychomotor domains. Integration in Islamic education also emphasizes the integrity of parenting, ie between the school, parents, and society. The implementation of the integrated Islamic education model in Hidayatullah Islamic Junior High School is well implemented, because it can provide a real improvement in the quality of the students.